ДИФФЕРЕНЦИРОВАНИЕ ДВУМЕРНЫХ И ТРЕХМЕРНЫХ АЛГЕБР ЗИНБИЕЛЯ - Камалов, У.; Хожабаева, Г.; Курбанбаев, Т. (SCIENCE and SOCIETY, 2024)
In this paper, we calculate the D matrix using multiplication tables of complex solvable 2,3-dimensional Zinbiel al- gebras. Basically, by calculating the multiplication tables in theorems 1,2, we get the results.